Fanau Manuia programme: key findings from a co-design process using a Pacific family-based approach to address pre-diabetes risk among Pacific children, New Zealand - Ridvan Tupai-Firestone; Barry Borman; Marine Corbin; Jeremy Krebs; Te Kani Kingi; Anna Matheson; Tupou Pulu; Ngaire Lerwill; Veisinia Pulu; Layla Latu; Nia Aitaoto; Prachee Gokhale; et al. (BMJ Public Health)
Introduction There is growing evidence that risk factors for pre-diabetes are becoming more prevalent in children, especially among Pacific populations in New Zealand. This research aimed to develop a family-based approach to address pre-diabetes risk in Pacific children.Methods 11 children of Pacific Islander descent at risk of pre-diabetes and their families were invited to co-design with the research team a health promotion programme to prevent the early onset of pre-diabetes. Families underwent an adapted version of an established empowerment and co-design programme initially developed for Pacific youth. A Pacific family-based approach was used to engage family members to enhance their individual and collective health capabilities. Comprised of two phases, the first phase was to co-create a health promotion programme that fit the lived realities of the families and was undertaken over 5 weeks. Families decided the goals they wanted to focus on and how these would be measured. The second phase was the implementation of the programme over 8 weeks.Results The families wanted the programme to have a nutritional aspect to access healthy foods; enhance family well-being through physical activities; and increase their knowledge and awareness of healthy lifestyles. The families designed a programme that focused on issues that were important to them and could be addressed in a holistic manner that was culturally relevant. Pre- and post-programme data included body mass index, waist-to-hip ratio, a questionnaire that looked at different facets of health and how they self-perceived it, and a logbook that chronicled their experience in the programme. Quantitative results had no statistical significance, but families saw a sense of increased well-being.Conclusion Family-based approaches to health promotion programmes need to be culturally relevant and focus on building the capacity of the whole family. This approach helps address key sociocultural challenges that are barriers to improved health outcomes.